1994
DOI: 10.1085/jgp.103.5.787
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Cl- current by hypotonic volume increase in human endothelial cells.

Abstract: We have used whole-cell and perforated patches to study ionic currents induced by hypotonic extracellular solutions (HTS, 185 mOsm instead of 290 mOsm) in endothelial cells from human umbilical veins. These currents activated within 30-50 s after application of HTS, reached a maximum value after ~50-150 s and recovered completely after re-exposing the cells to normal osmolarity. They slowly inactivated at potentials positive to +50 mV. The same current was also activated by breaking into endothelial cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(150 citation statements)
references
References 35 publications
9
140
1
Order By: Relevance
“…On the other hand, small conductance Cl-channels activated by HTS have been described in many cell types (< 4 pS; Kunzelmann, Kubitz, Grolik, Warth & Greger, 1992;Lewis, Ross & Cahalan, 1993;Nilius et al 1994a, b). Marunaka & Eaton (1990) (Christensen & Hoffmann, 1992), in MDCK cells (Banderali & Roy, 1992a) and also in proximal tubule cells from Necturus kidney (Fillipovic & Sackin, 1992 will shift the membrane potential to a value close to the equilibrium potential of the other ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, small conductance Cl-channels activated by HTS have been described in many cell types (< 4 pS; Kunzelmann, Kubitz, Grolik, Warth & Greger, 1992;Lewis, Ross & Cahalan, 1993;Nilius et al 1994a, b). Marunaka & Eaton (1990) (Christensen & Hoffmann, 1992), in MDCK cells (Banderali & Roy, 1992a) and also in proximal tubule cells from Necturus kidney (Fillipovic & Sackin, 1992 will shift the membrane potential to a value close to the equilibrium potential of the other ion.…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiological methods have been described in detail elsewhere (Nilius, Oike, Zahradnik & Droogmans, 1994a). Wholecell membrane currents were measured using ruptured patches or patches perforated with nystatin to avoid disturbance of the intracellular Ca2+-buffering mechanisms.…”
Section: Current Measurementsmentioning
confidence: 99%
“…2+ measurements have previously been described in detail (Nilius et al, 1994). Membrane potential was monitored in current clamp mode or controlled in voltage clamp mode with an EPC-9 (HEKA Elektronik, Lambrecht, Germany), using a nystatin-perforated patch (100 mg/ml).…”
Section: Electrophysiological Methods and Camentioning
confidence: 99%
“…Additionally, we found that prolonged exposure of endothelial cells to caffeine induces cell shrinkage. Although the mechanism underlying the caffeine-induced shrinkage is unknown, it has been shown that hypotonic volume increases activate a Cl-current in human endothelial cells (Nilius et al, 1994) suggesting that caffeine-sensitive, Ca2+-activated Cl-currents may regulate cell volume.…”
Section: Dependence Of Outward Currents On Extracellular Ca2+mentioning
confidence: 99%